Arms and the man [videorecording (DVD)] - Jones, James Cellan, 1931-; Bonham Carter, Helena, 1966-; Kensit, Patsy; Landen, Dinsdale; Markham, Kika; Torrens, Pip, 1960-; Ryecart, Patrick; Shaw, Bernard, 1856-1950; Davis, Desmond, 1926-2021-; Seyrig, Delphine, 1932-1990; Callow, Simon, 1949- (BBC Video ; Distributed in the USA and Canada by Warner Home Video, 2006)
One night, a frightened Swiss soldier of fortune climbs into the bedroom of a young Bulgarian girl and soon deflates her romantic notions about love and valor. The bonus play is set in 1796 at an inn where Napoleon rests at the start of his conquest of Italy.